Wider Inner Intercanthal Distance is a Predisposing Factor for Chronic Dacryocystitis in Adults - Most Morsheda Khatun; Mohd Rafiqul Islam; Rashed Mustafa; Shahin Sharmin; Mostarina Islam (KYAMC Journal, 2023)
Background: Many adult women of low socio-economic condition have been suffering from chronic dacryocystitis (CDC). Wider inner intercanthal distance (IICD) is a proposed risk factor for developing chronic dacryocystitis. A few studies have been undertaken in this regard. Objective: To find out the relationship between wider inner intercanthal distance and chronic dacryocystitis in adults. Materials and Methods: This cross-sectional comparative study was conducted in the Department of Anatomy, Rajshshi Medical College, Rajshshi, Bangladesh from July 2016 to June 2017. A total number of 460 subjects were enrolled for this study. Among them, 154 were patients of chronic dacryocystitis (CDC) and 306 were healthy controls. Their IICD was measured. Results: The mean IICD of CDC group was 30.71 ± 2.26 mm whereas the mean IICD of the control group was 29.20 ± 2.08 mm. The IICD of CDC patients was observed to be higher (p<0.001) compared to healthy controls. Conclusion: Those who had wider inner intercanthal distance were more predisposed to develop chronic dacryocystitis. So, wider IICD can be regarded as a risk factor for developing chronic dacryocystitis. KYAMC Journal Vol. 14, No. 02, July 2023: 83-86.